"Enjoyments, of a [. . .] more exquisite nature": Wordsworth and Commodity Culture - Anderson, Robert (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
Abstract This essay seeks to explore Wordsworth’s ambivalent relation to the commodity culture emerging in England around the turn of the Nineteenth-century. It does so by examining his unpublished poem "The Ruined Cottage" and his preface to Lyrical Ballads in two related contexts: the discourse of advertising and the history of consumer culture, including the institution of peddling. Wordsworth’s promise of the possibility of "enjoyments of. . . a more exquisite nature" available in his poetry if readers are willing to "give up much of what is ordinarily enjoyed" as poetry is similar to the structure of advertisement copy then as now: give up the product you now enjoy for a new and improved one. In the very essay in which he articulates a critique of industrialization and consumerism, Wordsworth unwittingly proposes a consumerist solution to the problem of consumerism. Drawing on the historical work of Colin Campbell and Neil McKendrick, this essay suggests that a dynamic similar to that operating in the preface holds for "The Ruined Cottage" as well. There is a distinct pattern in the poem, particularly in the Pedlar’s visits to Margaret, of intense but fleeting attachment which is similar to the process of consumption in which buyers form an intense attachment to a commodity which is abandoned a short time later as attachments to new products are formed. Far from being an example of the Romantic ideology in which poetry evades history, the poem can be seen as a Godwinian analysis of the ways which social forces and institutions "insinuate themselves" into the most intimate matters (82).